THE EFFECTIVENESS OF SELECTED AEROBIC TRAINING ON THE MENTAL HEALTH IN NON-ATHLETE POSTMENOPAUSAL WOMEN - Vahid Bakhshalipour; Afsaneh Sanatkaran; Siavash Khodaparast Sareshkeh; Zeinab Zivdar; Bisotoon Azizi (Sport Scientific And Practical Aspects, 2025)
Goals: Various problems occurs with the onset of menopause in women. The purpose of this study was to examine the effectiveness of selected aerobic training on the mental health in non-athlete postmenopausal women. Method: 40 postmenopausal women were selected by the convenience and purposive sampling. The instrument of this study was the General Health Questionnaire (GHQ-28). The collected data were analyzed by dependent and independent T-test, Wilcoxon test, chi-Square, and two-way ANOVA. Subjects’ training program was included 8 weeks running (3 sessions per week) in a 50-minute scheduling. Results: the mean score of intervention group was respectively 25.7±6.9 and 20.1±5.9 in the post-test and pre-test and it was respectively 24.5±6.9 and 25±7.8 in the control group. There was a significant effect in depression, social dysfunction, anxiety, and physical symptoms subscales in the experimental group (P<0.05). It was no significant in none of the subscales in the control (P>0.05). Conclusion: the results of this study showed that selected aerobic training led to improve and promote mental health in non-athlete postmenopausal women.